Comparative study of stent performance under combined loading - Mat Beyi, Abdul Fattah (2023)
A coronary artery stent is a medical device used to treat coronary artery disease. In the long term, there is a chance of restenosis, or stent fracture. Stainless steel, which has excellent mechanical properties, is the most common material for conventional stents. Because of their high yield stress and ductility, stainless steel stents can be safely extended. Stainless steel stents are permanent in the body and can cause complications. These studies, however, address the behaviour of stents under single and combined loading in terms of stress and strain. A new stent is constructed and tested under this loading. Computational analysis can be used to determine mechanical performance, anticipate possible problems, and direct stent optimization. As a result, preliminary evaluation using numerical methods enables a more in-depth analysis of some aspects of mechanical performance. In this thesis, six different stent designs (Palmaz, AVE S660, Bx Velocity, Multilink, Express and NIR) were evaluated. Best stent design in term of stress would be selected and then structure of the stent would be optimized. In Explicit numerical analysis, the deformation of the designs was simulated using ANSYS under internal pressure. AVE S660 stent shown most reaction as it shrinks to the middle while the highest and lowest von Mises stress is 352MPa and 190MPa for NIR and Express stent, respectively. The mechanical performance of a new design stent based on the previous evaluations was investigated in this study under single and combined loading